FORMING THE CONCEPTS OF KNOWLEDGE MANAGEMENT MODEL IN AN ORGANIZATION: THEORETICAL-METHODOLOGICAL APPROACH (basing on empirical research) - G. I. Gumerova; E. S. Shaimiyeva (Russian Journal of Economics and Law)
Objective: 1. To define the main provisions of the knowledge management model in an organization. 2. To form the characteristics of knowledge markets. 3. To analyze the knowledge market in 2000–2010 in the Russian Federation. Methods: general scientific methods of theoretical and empirical cognition Results: knowledge management is analyzed within the frameworks of knowledge management system at micro-, meso- and macrolevels; knowledge is classified as an object of management in micro-, meso- and macrosystems; analysis methodology is suggested, basing on the existing statistical material; trends of knowledge market development in industrially developed mesosystems of the Russian Federation are defined. Scientific novelty: the knowledge management model is formed; the methodology of knowledge management analysis at micro-, meso- and macrolevels is suggested, with the formed indicators of knowledge markets measurement at relevant levels; dynamics of development of the apparent and non-apparent knowledge in the Russian Federation is revealed for 2000–2010, which consists in dominating of non-apparent knowledge market development; the leading position of the Central Federal District in the knowledge management market as the industrially developed mesosystem. Practical value: theoretical value – systematization and elaboration of theoretical provisions for the model, the methodology of knowledge management at micro-, meso- and macrolevels; appied value - analysis of the knowledge market to increase the efficiency of knowledge management market at micro-, meso- and macrolevels during elaboration, production and commercialization o f knowledge by the Russian enterprises.